Ways To Improve The Quality Of Educational Services Using ICT - Barno Akhmedova (Genius Journals, 2022)
At present, the main direction in the digitization of education is the creation of pedagogical software tools for various disciplines using ICT. However, pedagogical software tools based on existing and developing computer technology are not sufficient as an educational service in terms of teaching. One of the reasons for this is that computer technology has begun to be introduced into the traditionally organized learning process, and in terms of its content and style, this technology is not clearly targeted.
Keywords: educational service; intellectual potential; l, improving the quality of educational services; innovation